Strategic CSR in Asymmetric Cournot Duopoly - Lisa Planer-Friedrich; Marco Sahm (Journal of Industry, Competition and Trade, 2020)
We examine the strategic use of corporate social responsibility (CSR) in Cournot competition between two firms that differ in their marginal costs of production. The level of CSR determines the weight a firm puts on consumer surplus in its objective function before it decides upon supply. We show that the more efficient firm chooses a higher CSR level, reinforcing its dominant position. If there are sufficiently large fixed costs of CSR, only the more efficient firm will engage in CSR.
Keywords: D43; L13; L21; L22; 690; Corporate social responsibility; Cournot duopoly; Asymmetric costs; Heterogenous firms